Stockholm Birth Cohort - Almquist, Ylva B. (Stockholm University, 2014)
The Stockholm Birth Cohort Study (SBC) was created in 2004/2005 by a probability matching of two anonymized longitudinal datasets; The Stockholm Metropolitan study and The Swedish Work and Mortality Database (WMD). The former involves all children born 1953 that lived in the Stockholm metropolitan area as of November 1, 1963, while the latter comprises data for the period 1980-2009 on all individuals living in Sweden in 1980 or 1990, and born before 1986.

The study comprises data from both surveys and public register records. The core of the project consists of three surveys from The Stockholm Metropolitan study; The School Study (1966), The Family Study (1968), and The Culture and Leisure Time Study (1985). There is also a wide range of register data, for instance delivery records, occupational and income data, welfare recipiency data, health records, mortality data, educational data, and dependency and child welfare committee data.

The Stockholm Birth Cohort offers unique opportunities for longitudinal research within various fields such as sociology, public health science, and psychology. So far the datasets have resulted in more than 140 publications which have dealt with, among other things, whether and how childhood circumstances affect later social outcomes in adult life.

Purpose:

To aim is to create a new tool for life-course studies of health outcomes as well as social outcomes for research in fields such as psychology, public health science, and sociology.

Studien “Född i Stockholm på femtiotalet” skapades 2004/2005 genom en sannolikhetsmatchning av två anonymiserade statistiska datamaterial; Metropolitprojektet och databasen Hälsa, sjukdom, arbete och inkomst (HSIA). Den förra innefattar alla barn födda 1953 och som bodde i Stockholm 1963, och den senare består av uppgifter för perioden 1980-2009 över alla personer som bodde i Sverige 1980 eller 1990 och som var födda före 1986.

Studien består av data från både enkäter och allmänna register. Ryggraden för hela projektet utgörs av tre enkätundersökningar inom ramen för Metropolitprojektet; Skolundersökningen (1966), Familjeundersökningen (1968) och Kultur- och fritidsenkäten (1985). Därtill utgörs innehållet av data från en rad olika register, däribland förlossningsjournaler, inkomster och yrkesuppgifter, socialbidrag, hälsa, dödsorsaker, utbildning och information om familjen från socialregister.

"Född i Stockholm på femtiotalet" erbjuder en unik möjlighet att bedriva longitudinell forskning inom flera discipliner såsom sociologi, folkhälsovetenskap och psykologi. Hittills har datamaterialet resulterat i över 140 publikationer, och har till exempel använts för att undersöka bestämmelsefaktorer för barns möjligheter i livet.

Syfte:

Syftet är att skapa ett nytt redskap för livsförloppsstudier av hälsoutfall och sociala utfall för forskning inom discipliner såsom psykologi, folkhälsovetenskap och sociologi.
Född i Stockholm på femtiotalet
Keywords: housing; boende; population migration; migration; politics; politik; religion; religion; social mobility; social rörlighet; social problems; sociala problem; culture; kultur; consumption; konsumtion; ageing; åldrande; health; hälsa; personality; personlighet; social welfare; social välfärd; residential mobility; flyttningsbenägenhet; family environment; familjemiljö; human behaviour; mänskligt beteende; income distribution; inkomstfördelning; social inequality; social ojämlikhet; social structure; social struktur; wages; löner; housework; hushållsarbete; social services; socialtjänst; parental role; föräldraroll; child care; barnomsorg; citizenship skills; medborgerliga färdigheter; political action; politisk handling; unemployment; arbetslöshet; family life; familjeliv; political interest; politiskt intresse; political behaviour; politiskt beteende; attitudes; attityder; drinking behaviour; alkoholvanor; television; television; radio; radio; social reform; social reform; public services; offentlig service; hobbies; hobbyer; news; nyheter; advertising; reklam; economic conditions; ekonomiska villkor; income; inkomst; social class; social klass; ill health; ohälsa; housing facilities; bostadskomfort; diseases; sjukdomar; dental health; tandhälsa; labour and employment; arbete och sysselsättning; holidays; semesterresor; political participation; politiskt deltagande; marital status; civilstånd; population; befolkning